Effect of oxygen concentration on combustion behavior of single coal pellets from three different ranks in a concentrating photothermal reactor. (1st June 2020) - Li, Hanjian; Chi, Huanying; Hu, Song; Song, Gongxiang; Leong, Huini; Xu, Kai; He, Limo; Wang, Yi; Su, Sheng; Xiang, Jun
Abstract: Comparative combustion studies were performed in a concentrating photothermal platform (room temperature chamber type experimental bench with less volumetric reactions) on coal pellets (>6mm) from three different ranks: bituminous coal, sub-bituminous coal, and lignite. The combustion of single coal pellet in 21 ~ 50% oxygen concentration was observed with IR pyrometry and high-speed cinematography to obtain temperature–time–size histories. Based on the combined mass measurement and gaseous product analysis, a comprehensive understanding of the effects of oxygen concentration on single coal pellet combustion behaviours was developed. Distinctive three-stage processes were proposed with characteristical temperature and cinematography variations. No obvious flame duration was detected in 21% or 30% O2 while transient but luminous flames were clearly observed in 40% and 50% O2 and formed notable temperature peaks in the second stage during combustion of all the three ranks coal pellets. Volume and density both changed non-linearly during combustion and such processes were accelerated with the increase of oxygen concentration. High concentrations of CO and CH4 were detected due to the suppression of volumetric reactions. CO accounted for about 9.3% of the gaseous products and consistently exhibited two peaks with the first peak independent from oxygen concentration. Three-stage combustion process was further validated by CO2 /CO ratio and the effective reaction orders of oxygen concentration were 1.91 (bituminous coal), 1.81 (sub-bituminous coal) and 1.26 (lignite).